An Analytical Model for Evaluating the Hydraulic Conductivity of the Fracture‐Conduit‐Matrix System - Zhang, Shuai; Liu, Xiaoli; Wang, Mingyang; Wang, Enzhi (Geophysical research letters, 2025)
In the fracture‐conduit‐matrix system, distinct shape differences among water‐conducting channels (fractures and conduits) hinder developing an analytical model for flow characteristics and hydraulic conductivity assessment. To address this, we introduce the elliptic‐conduit‐matrix model (ECMM) under velocity slip interface conditions. This analytical model, adaptable to elliptical axis and matrix permeability variations, can be reduced to fracture‐matrix model, conduit‐matrix model, smooth elliptic (circular) pipes, and smooth fractures. Direct numerical simulations on flow in single, multi, and mixed channel‐matrix systems (varying channel counts and matrix permeabilities) validated the ECMM, demonstrating a higher precision compared to the previous models. Plain Language Summary The fracture‐conduit‐matrix system (or triple porous system) is a complex system where water flows through different channels, like fractures and conduits. However, the varying shapes of these channels make it difficult to develop an analytical model to understand how water flows through the system. This study introduces an elliptic‐conduit‐matrix model to address this challenge. The elliptic‐conduit‐matrix model is a new approach to understanding fluid flow in the triple porous system. The model can adapt to different channel shapes and system properties, and its accuracy has been validated through simulations. This knowledge can be valuable for various applications related to geophysics and engineering, where understanding fluid flow in complex systems is important. Key Points The fluid coupling between conduits/fractures and matrix is achieved An analytical model for evaluating the hydraulic conductivity of fracture‐conduit‐matrix system is developed The analytical model can evolve into existing classic models